Volumetric Assessment of Extratemporal Structures in Patients With Temporal Lobe Epilepsy - Asadollahi, Marjan; Rahimian, Elham; Asadi-Pooya, Ali Akbar; Tahsini, Majid; Huppertz, Hans-Jürgen; Akbari, Nayyereh; Simani, Leila (International Clinical Neuroscience Journal, 2022)
Background: We assessed the presence of brain volume loss in the extratemporal structures in patients with temporal lobe epilepsy (TLE). The associations between brain volume loss in these structures and epilepsy duration, magnetic resonance imaging (MRI) findings, and occurrence of focal to bilateral tonic-clonic seizures (TCS) were assessed. Methods: In this cross-sectional study, all adult patients with drug-resistant TLE, who were admitted to the epilepsy monitoring unit at Loghman-Hakim Hospital, Tehran, Iran, during 2016-2020, were included. For all the participants, brain MRI was performed and patients with TLE were divided into two subgroups of those with hippocampal sclerosis (TLE-HS) and patients with normal-appearing brain MRI findings (TLE-no). Independent sample t test was applied to compare quantitative variables in the study groups. Pearson correlation test examined the correlation between the clinical and volumetric features. Results: 203 participants (81 patients with TLE and 122 healthy controls) were studied. Compared with healthy controls, patients with TLE showed a decrease in their midbrain (P = 0.02) and thalamus (P = 0.01) volume. The degree of thalamic atrophy was more significant in TLE-HS (P = 0.03). Moreover, the degree of midbrain volume loss was more significant (P = 0.07) in patients who had TCS in the past two years (N = 31) compared with those who did not (N = 50). The volume of the thalamus (r: -0.252, P = 0.02) and pallidum (r: -0.255, P = 0.02) had inverse correlations with the epilepsy duration. Conclusion: Patients with TLE have lower midbrain and thalamus volume compared with the healthy controls, which may be attributed to the seizure-induced injury. Midbrain atrophy may theoretically increase the risk of sudden unexpected death in epilepsy (SUDEP) because of the enhanced autonomic dysfunction.